Representations of Diversity in Classroom Resources: “Windows and Mirrors” or Cracked Glass? - Golden, Rebecca (My University, 2022)
"I am a Newly Qualified Teacher (NQT), recently graduated from Marino Institute of Education. My specific interest in intercultural education arose two years ago while studying the module as part of the Bachelor of Education course. My lecturer made reference to a quote from Carol Buehner (n.d.): “in years to come, children may not remember everything they learned in your classroom, but they will remember how they felt”. This quote really resonated with me, and I became inspired to develop my own knowledge, skills, and confidence in order to effectively implement inclusive practice in my future teaching career. Following my teaching experience in two Community National Schools, my passion for diversity and inclusion increased further. My dissertation focussed on the representations of migration-related diversity in classroom resources, which has helped me in becoming competent and confident in teaching the increasing number of students from diverse ethnic and racial backgrounds now in Irish classrooms and provided me with a huge insight into the implications of teaching in these multicultural settings."
Keywords: Primary Education; Diversity; Representation; Immigration; Resources; Research Subject Categories::SOCIAL SCIENCES; Education--Ireland